Perfil da repolarização cardíaca em indivíduos com lesão medular cervical praticante de exercício físico - Santos, Roberto (2015)
The aim of present study were: 1) to compare rest QT and QTc intervals in trained men with and without cervical spinal cord injury (CSCI), and 2) to investigate cardiac ECG parameters in trained men with CSCI submitted to maximal effort test. Thirty men were separated into three groups: Control (CON, 25.3 ± 4.1 yrs, 179.2 ± 7.4 cm, 82.3 ± 8.1 Kg; BMI 26.3 ± 2.3 2 kg/m , strength training of 3 days/week; aerobic training 1day/week; n=10) without CSCI, High volume exercise (HVE, 30.5 ± 4.3 yrs, 173.0 ± 11.1 cm, 65.7 ± 8.1 Kg; BMI 22.0 ± 2.9 2 kg/m , 3 day/week rugby specific exercises, 60min/day; n=12) and Moderate volume of 2 exercise (MVE, 33.7 ± 5.9 yrs, 178.1 ± 4.3 cm, 73.6 ± 9.6 Kg; BMI 23.1 ± 2.5 kg/m , 2 days/week specific rugby exercises, 60 min/day; n=8) with incomplete CSCI (C5-C7) more than 12 months. ECG was recorded (1 KHz, 12-bit resolution, 12 lead) in rest, during and after effort test. Heart rate, QT, corrected QT, PR interval and QRS duration were measured. QT interval was significantly reduced (p = 0.001) in the HVE compared to CON. QTc interval showed no difference between MVE vs. HVE (p>0.05). No changes were observed in QT, QTc, PRS and QRS between rest and post effort (p>0.05). Effort test does not change ECG parameters in CSCI subjects. A high volume of week exercise program promotes abnormalities in cardiac repolarization of these patients compared to a moderate training program.